The Crusades - DeCarlo, Carolyn (Empires in the Middle Ages., 2018)
Chronicles the centuries-long period of crusades, or military campaigns to take control of the Holy Land from the Muslims. Discusses important political events, leaders, culture, and society. Includes a glossary, resources for further information, and an index.